Arrhythmia Curve Interpretation Using a Dynamic System Model of the Myocardial Pacemaker - Ikeda, N.; Takayanagi, K.; Takeuchi, A.; Nara, Y.; Miyahara, H. (Methods of Information in Medicine, 1997)
A problem of identifying the phase response curve of the myocardial pacemaker was investigated using a simple dynamic system model of cardiac arrhythmia. A hybrid optimization method of a genetic algorithm and a local optimization technique was employed to obtain a solution of the model fitting. The method was applied to two categories of arrhythmias, ventricular parasystole and high-degree AV block. The present study offered a new insight into the mechanism of cardiac arrhythmias.
Keywords: Arrhythmia; Phase Response Curve; Ventricular Parasystole; High-degree AV Block